Pengaruh Corporate Governance Terhadap Pelaporan Online Informasi Strategik Pada Perusahaan Yang Terindeks LQ45 - Zul Azmi; Neng Murialti (Akuntansi & Ekonomika, 2018)
This study aims to examine corporate governance mechanism on online reporting of strategic information. To carry out this study, some of the company’s specific characteristics are used as control variables such as firm size, firm complexity, risk level and profitability. The sample of this research is taken from a company indexed LQ45 in Indonesia Stock Exchange. Hypothesis tested by using cross sectional data with multiple regression. The result show that audit committe are positively assosiated with strategic information online reporting. The frequency of meeting of the board of directors and the size of the auditor that include the big four or local has no effect on the online reporting strategic information. The proportion of independent non-executive directors shows a negative direction in terms of online reporting of strategic information. Keywords: Corporate governance, Online Reporting, Audit Committee JEL Classification:M41, G30